2018
DOI: 10.1074/jbc.ra118.003004
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the fih gene encoding an inhibitor of hypoxia-inducible factors increases hypoxia tolerance in zebrafish

Abstract: Many aerobic organisms have developed molecular mechanism to tolerate hypoxia, but the specifics of these mechanisms remain poorly understood. It is important to develop genetic methods that confer increased hypoxia tolerance to intensively farmed aquatic species, as these are maintained in environments with limited available oxygen. As an asparaginyl hydroxylase of hypoxia-inducible factors (HIFs), factor inhibiting HIF (FIH) inhibits transcriptional activation of hypoxia-inducible genes by blocking the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…In fact, we recently demonstrated that GSB is a highly euryoxic fish, capable of adjusting the mitochondrial machinery to cope with a decreased basal metabolic rate, when hypoxia-challenged [70]. The concomitant down-regulation of the hif1α inhibitor in the current study could help to tolerate the hypoxia, as this was previously demonstrated experimentally in zebrafish, when the fih gene encoding an inhibitor of hypoxia-inducible factors was deleted [71].…”
Section: Discussionsupporting
confidence: 68%
“…In fact, we recently demonstrated that GSB is a highly euryoxic fish, capable of adjusting the mitochondrial machinery to cope with a decreased basal metabolic rate, when hypoxia-challenged [70]. The concomitant down-regulation of the hif1α inhibitor in the current study could help to tolerate the hypoxia, as this was previously demonstrated experimentally in zebrafish, when the fih gene encoding an inhibitor of hypoxia-inducible factors was deleted [71].…”
Section: Discussionsupporting
confidence: 68%
“…These two enzymatic-deficient mutants had no obvious effect on the activity of the HRE reporter induced by either hif-1aa or hif-2aa (Supplemental Fig. 3A, 3B), validating their enzymatic-dead activity (47). Overexpression of the two mutants significantly inhibited the activity of four promoters induced by WT irf7, similar to overexpression of WT phd3 (Fig.…”
Section: Zebrafish Phd3 Negatively Regulates Antiviral Response Mainly Through Suppressing Irf7 Transactivity Independent Of Its Prolyl Hsupporting
confidence: 58%
“…However, different animal species appear to have evolved different tolerances to hypoxia. For example, some aquatic species such as zebrafish can tolerate complete anoxia during development with no apparent adverse effects, although the differential responses by different species, and the mechanisms, are poorly understood (Mendelsohn et al, 2008, 2009; Cai et al, 2018).
Fig.
…”
Section: Evidence From Evolution and From Normal Development Links Hymentioning
confidence: 99%